2021
DOI: 10.3390/nu13103368
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Vitamin D and Zinc Status and the Progression of Clinical Symptoms among Outpatients Infected with SARS-CoV-2 and Potentially Non-Infected Participants: A Cross-Sectional Study

Abstract: Vitamin D and zinc are important components of nutritional immunity. This study compared the serum concentrations of 25-hydroxyvitamin D (25(OH)D) and zinc in COVID-19 outpatients with those of potentially non-infected participants. The association of clinical symptoms with vitamin D and zinc status was also examined. A checklist and laboratory examination were applied to collect data in a cross-sectional study conducted on 53 infected outpatients with COVID-19 and 53 potentially non-infected participants. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…Falagas et al assessed sex differences in the occurrence and severity of respiratory tract infections and showed that females were more usually influenced by infections of the upper respiratory tract; however, males were more commonly influenced by infections of the lower respiratory tract [ 24 ]. In line with our results, another study revealed that the odds ratio of neurologic symptoms of COVID-19 in males was 0.41 times that in females in the same follow-up period [ 7 ]. In line with our findings regarding sex effect on severity and incidence of COVID-19 symptoms, Alwani et al investigated sex-based differences in severity and mortality in COVID-19.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Falagas et al assessed sex differences in the occurrence and severity of respiratory tract infections and showed that females were more usually influenced by infections of the upper respiratory tract; however, males were more commonly influenced by infections of the lower respiratory tract [ 24 ]. In line with our results, another study revealed that the odds ratio of neurologic symptoms of COVID-19 in males was 0.41 times that in females in the same follow-up period [ 7 ]. In line with our findings regarding sex effect on severity and incidence of COVID-19 symptoms, Alwani et al investigated sex-based differences in severity and mortality in COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…Serum concentrations of TSH, T3, and T4 were measured using an IDEAL kit (IDEAL, Tehran, Iran) following the ELISA method. The researcher gathered information on the patients’ clinical symptoms (from positive-PCR group outpatients) via phone on the 7th, 14th, 21st, and 28th days [ 7 , 8 ]. All symptoms fell into four categories: general, pulmonary, gastrointestinal, and neurologic symptoms [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to maintain the immune system, it is important to maintain the amount of exercise that does not cause excessive stress to the body, and to provide adequate nutritional intake and rest [8,108,[111][112][113][114][115][116][117] (Figure 3), which were also explained by a digest version in an easy-to-understand manner [118]. Furthermore, it is recently suggested that moderate exercise and physical activity is effective, even for the recovery from COVID-19, suggesting the importance of exercise in the rehabilitation of the disease as well [119,120].…”
Section: Exercise and Nutrition Under The Spread Of Covid-19 Infection And Consequent Lockdown Restrictionsmentioning
confidence: 99%
“…It also lower the management costs Frequent urination, vomiting, fever, dysuria, and hematuria are possible side effects. [5][6] This method may lower the misuse of antibiotics and hence lower management costs. The first line of defense against the bacteria is epithelium derived cathelicidin,.…”
Section: Introductionmentioning
confidence: 99%